A decoupling perspective on circular business model implementation: Illustrations from Swedish apparel. (10th January 2018) - Stål, Herman I.; Corvellec, Hervé
Abstract: Drawing on the concept of decoupling, from institutional theory in organizational studies, this paper explains how organizations mitigate demands for circularity. Seven Swedish apparel companies that have started collecting used clothes as a form of engagement with circular business models serve as case studies. The paper shows how outsourcing and internal separation allow these companies to buffer their business model and core way of creating value from emerging demands. It also shows how companies pro-actively work at influencing institutional demands for circularity by making these demands compatible with their own interests. The concept of decoupling thereby provides key insights into the development and implementation, or absence thereof, of circular business models. Highlights: Decoupling allows firms to buffer business models from institutional demands. Outsourcing and internal separation are means of decoupling. Decoupling allow firms to showcase rather than truly adopt circular economy. Firms influence institutional demands to appear circular but remain linear.